2011
DOI: 10.1111/j.1365-2133.2011.10481.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of linear IgE deposits in bullous pemphigoid and mucous membrane pemphigoid: a useful clue for diagnosis

Abstract: Our findings indicate that demonstration of tissue-bound IgE deposits provides an additional useful criterion for diagnosis of BP and MMP in some patients. Prospective studies are needed to better correlate the presence of tissue-bound and circulating IgE autoantibodies and their specificity with distinct clinical features and course of BP and MMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 16 publications
1
49
2
Order By: Relevance
“…[82,83] Provost and Tomasi first described weak linear IgE deposition along the BMZ in 25% of patients, [82] …”
Section: Skin-bound Ige Anti-bmz Autoantibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[82,83] Provost and Tomasi first described weak linear IgE deposition along the BMZ in 25% of patients, [82] …”
Section: Skin-bound Ige Anti-bmz Autoantibodiesmentioning
confidence: 99%
“…[79] The percentage of BP patients with IgE anti-BP180 NC16A autoantibodies varied substantially in the different reports. [46,83,95,96,[99][100][101][102][103][104][105][106] In the initial report, we identified anti-BP180 NC16A IgE reactivity in 55% of 18 BP sera. [96] Subsequent studies found IgE anti-NC16A in 100% of 10, 83% of 18, 22% of 37, 77% of 43, 30% of 67, 61% of 31, and 71% of 56 BP patients.…”
Section: Bp180-specific Ige Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In BP, both IgG-and IgE-class autoantibodies specific for BP180 are found in the circulation and bound to the basement membrane zone (BMZ) of affected skin. (1)(2)(3)(4) These two classes of autoantibodies, which have been shown to target the same cluster of epitopes located within the non-collagenous 16A region (NC16A) of BP180, are produced by the vast majority of BP patients (IgG, 94% of patients; IgE, > 85%). (1,(5)(6)(7) Early work probing the pathogenesis of BP in in vitro and in vivo models demonstrated a role for IgG class autoantibodies (6,(8)(9)(10) ; however, none of these IgG-based models were able to recapitulate the early phase of lesion development in the human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the association with tissue bound IgE with urticarial papules and plaques in patients with bullous pemphigoid have been reported [4], Moriuchi et al reported there were no differences between in vivo IgE-positive and IgE-negative cases, not only in disease severity but also in clinical course and outcome [5]. However, these studies were performed by direct immunofluorescence and the IgE antibodies were tissue-bound, not circulating autoantibodies.…”
mentioning
confidence: 96%